2020
DOI: 10.1101/2020.03.06.981290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methyltransferase 1 (DNMT1) function is implicated in the age-related loss of cortical interneurons

Abstract: 36Increased life expectancy in modern society comes at the cost of age-associated disabilities and 37 diseases. Aged brains not only show reduced excitability and plasticity, but also a decline in 38 inhibition. Age-associated defects in inhibitory circuits likely contribute to cognitive decline and age-39 related disorders. Molecular mechanisms that exert epigenetic control of gene expression, contribute 40 Running Title 2 This is a provisional file, not the final typeset article to age-associated neuronal im… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 123 publications
1
9
0
Order By: Relevance
“…Due to their larger soma size, the dynamics and the temporal course of perinuclear HTT aggregation can be clearly identified by live cell imaging, in contrast to aggregation in the smaller-sized and roundish N2a cells. In line with our findings that Dnmt1 siRNA application increased the velocity of retrograde transport [ 11 ], we found that the formation of HTT-GFP aggregates was significantly faster upon siRNA-mediated depletion of Dnmt1 in CB cells ( Figure 4 ). This indicates that DNMT1 is involved in mutant HTT-induced cytotoxicity via modulation of aggresome formation by acting on retrograde transportation.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Due to their larger soma size, the dynamics and the temporal course of perinuclear HTT aggregation can be clearly identified by live cell imaging, in contrast to aggregation in the smaller-sized and roundish N2a cells. In line with our findings that Dnmt1 siRNA application increased the velocity of retrograde transport [ 11 ], we found that the formation of HTT-GFP aggregates was significantly faster upon siRNA-mediated depletion of Dnmt1 in CB cells ( Figure 4 ). This indicates that DNMT1 is involved in mutant HTT-induced cytotoxicity via modulation of aggresome formation by acting on retrograde transportation.…”
Section: Resultssupporting
confidence: 91%
“…In previous studies, we identified that DNMT1 transcriptionally controls a variety of endosomal, lysosomal, and retrograde trafficking-associated genes in their expression, with most of them being repressed by DNMT1 in cortical interneurons [ 11 , 12 ] ( Figure 1 a and Supplementary Figure S1a ). Functionally, we confirmed that DNMT1 slows down the velocity of retrograde transportation of endolysosomal compartments in cerebellar granule (CB) cells [ 11 ], which we frequently use as a neuronal cell culture model [ 11 , 12 ]. Here, we verified whether retrograde transport is likewise modulated by DNMT1 in neuroblastoma (N2a) cells, in order to assess whether the regulation of retrograde transport is a more general, cellular sub-type independent function of DNMT1.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations